An investigation of mindfulness, adolescent psychopathology and regulatory emotional self-efficacy - Miller, Reagan L., author; Lucas-Thompson, Rachel, advisor; Coatsworth, J. Douglas, advisor; Prince, Mark, committee member (Colorado State University. Libraries, 2021)
A robust body of literature suggests that mindfulness benefits mental health and psychological well-being, but the majority of this research has only been conducted among adults; also, mechanisms that link these two concepts are not fully understood. Mindfulness is theoretically expected to reduce psychopathology through more effective emotion regulation and, as a result, greater beliefs about one's ability to regulate their own emotions; therefore, regulatory emotional self-efficacy (RESE) is a likely mediator of this relationship. In order to comprehensively understand the relationship between the variables, however, two theoretical models were tested; RESE was first tested as a meditator and secondarily tested as a predictor of mindfulness. Among a sample of 149 adolescents (14-21 years old), bias-corrected bootstrapped estimates revealed that RESE was not found to be a mediator in the relationship between mindfulness and adolescent psychopathology. RESE was, however, a better predictor of mindfulness and subsequent reductions in adolescent psychopathology. These results suggest that mindfulness and RESE work together to reduce adolescent psychopathology and that adolescents may need to have effective management of their emotions before being able to practice mindfulness. Going forward, the investigation of additional mediators, as well as multiple facets of mindfulness among a more diverse and longitudinal sample, warrants further investigation.
Keywords: mindfulness; adolescence; psychopathology